Dynamic impacts of lockdown on domestic violence: Evidence from multiple policy shifts in Chile - Sonia R. Bhalotra; Emilia Brito; Damian Clarke; Pilar Larroulet; Francisco Pino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We leverage staggered implementation of lockdown across Chile's 346 municipalities, identifying dynamic impacts on domestic violence. Using administrative data, we find lockdown imposition increases indicators of distress related to domestic violence, while decreasing domestic violence reports to the police. We identify male job loss as a mechanism driving distress, and female job loss as driving decreased reporting. Stimulus payments to poor households act on both margins, their impacts partially differentiated by lockdown status. Once lockdown is lifted, police reports surge but we see a ratchet effect in distress. Our findings accentuate the controversy around welfare impacts of lockdown mandates.
Keywords: J12; I38; H53; 330; domestic violence; social safety net; public health; COVID-19